The World Bank's View of Early Childhood - PENN, HELEN (Childhood (Copenhagen, Denmark), 2002)
This article explores the World Bank's view of early childhood as an example of the globalization of childhood. It argues that the Bank pursues neoliberal economic policies that exacerbate the gap between rich and poor nations and between the rich and poor within countries. These policies affect children's lives adversely, but they are legitimized by the Bank in a variety of ways. The Bank claims to have children's interests at heart, and identifies early childhood as a fruitful site for interventions. It draws on traditional Anglo-American notions of family, community and childhood in its justification for these interventions. The article explores the inherent contradictions in these policies towards young children.